2017
DOI: 10.1088/1741-4326/aa4f5e
|View full text |Cite
|
Sign up to set email alerts
|

Resonant and non-resonant internal kink modes excited by the energetic electrons on HL-2A tokamak

Abstract: Strong resonant and non-resonant internal kink modes (abbreviated as RKs and NRKs, respectively), which are also called resonant and non-resonant fishbones, are observed on HL-2A tokamak with high-power ECRH  +  ECCD− (or ECRH) and ECRH  +  ECCD+, respectively. (‘Resonant’ derives from the existence of q  =  1 surface (the resonant surface), and ‘non-resonant’ originates from the absence of q  =  1 surface (). ECCD+ and ECCD− mean the driving direction of energetic electrons is the same and opposite to plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 32 publications
0
29
0
2
Order By: Relevance
“…We investigate the well-understood positive shear safety factor profile first, to validate our results. Then, we increase q 0 from 0.94 to 0.99 then 1.01, to investigate the non-resonant mode [26] regime of q 0 > 1 with no q = 1 rational surface existing. It is found that even if the mode is non-resonant due to the absence of q = 1 surface, it is still unstable due to energetic ions drive.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…We investigate the well-understood positive shear safety factor profile first, to validate our results. Then, we increase q 0 from 0.94 to 0.99 then 1.01, to investigate the non-resonant mode [26] regime of q 0 > 1 with no q = 1 rational surface existing. It is found that even if the mode is non-resonant due to the absence of q = 1 surface, it is still unstable due to energetic ions drive.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The non-resonant e-fishbone modes are driven on HL-2A tokamak with high power ECRH and co-ECCD. [56] The co-ECCD means driving direction of ECCD is the same to plasma current. Unlike resonant e-fishbone modes with periodic strong bursting amplitude and rapid chirping-down frequency, non-resonant modes always have saturated amplitudes and keeps for a long time, as shown in Fig.…”
Section: Reviewmentioning
confidence: 99%
“…In HL-2A, the ECEI diagnostic has been extensively used to detect the 2D structure of large scale MHD modes [10,11,15,16], such as tearing mode, fishbone, and sawtooth crash. Figure 7 shows the mode structure of the m/n=2/1 tearing mode.…”
Section: Multi-scale Interaction Between Tm and Turbulencementioning
confidence: 99%